Milkman - Burns, Anna, 1962- (Faber & Faber Limited, 2018)
"In this unnamed city, to be interesting is dangerous. Middle sister is our protagonist. She is busy attempting to keep her mother from discovering her nearly-boyfriend and to keep everyone in the dark about her encounter with Milkman (which for the life of her, she cannot work out how it came about). But when first brother-in-law, who of course had sniffed it out, told his wife, her first sister, to tell her mother to come and have a talk with her, middle sister becomes 'interesting'. The last thing she ever wanted to be. To be interesting is to be noticed and to be noticed is dangerous. Milkman is a searingly honest novel told in prose that is as precise and unsentimental as it is devastating and brutal. A novel that is at once unlocated and profoundly tethered to place is surely a novel for our times"--